Temporal Variability in Call Rates of Weddell ( Leptonychotes weddellii ) and Leopard ( Hydrurga leptonyx ) Seals Near Davis Station, East Antarctica - Emma A. Simmonds; John M. Terhune; Brian S. Miller; John van den Hoff (Marine Mammal Science, 2026)
We investigated Weddell seal ( Leptonychotes weddellii ) and leopard seal ( Hydrurga leptonyx ) vocalizations using passive acoustic monitoring beneath landfast ice and open water, 5.6 km seaward from Davis Station, East Antarctica. Eight‐minute recordings were manually sampled at 1 h intervals over 24 h every 10 days from 24 July 2021 to 30 January 2022. Call counts for Weddell seals were highest in the winter, lower during the breeding season, and almost absent in the summer. This change coincided with the occurrence of open water over the recording site, a progressive shift in Weddell seal behavior from foraging to aggregating in local fjords for the annual pupping, mating, and molting periods, and an increase in leopard seal—a potential predator—call detection rates. Leopard seal calls were primarily detected in December after the landfast ice broke up. In winter, Weddell seal calling counts were highest at dusk and night, and lowest during the day when the seals may have been feeding. Neither species exhibited a diel calling pattern once there were 24 h of sunlight. Seal locations were associated with the presence and absence of landfast ice, and call detections were influenced by their distances to the recorder.